Cantonal opioid agonist treatment authorisation systems – a mixed-method qualitative investigation (Swiss Medical Weekly, 2024)
BACKGROUND AND AIM: In Switzerland, a cantonal authorisation is required to introduce opioid agonist treatments (OAT). We investigated and compared the terms of these cantonal OAT authorisations throughout Switzerland. The primary objective was to determine how the overseeing cantonal officials implemented and perceived the legal requirements.METHOD: We started with a cross-sectional analysis of legal texts and cantonal OAT guidelines. Based on the document analysis, we conducted 26 semi-structured interviews with the cantonal officials who grant OAT authorisations.FINDINGS: In most cantons (21 of 25), the OAT authorisation is specific to the person treated and must be renewed every year. Today, 21 cantons either have implemented or are implementing the same web-based software to process and manage OAT authorisation requests. Cantons have implemented diverging requirements regarding, amongst others, the involvement of third parties in OAT and the training required of prescribing physicians. Lastly, the OAT process does not seem to be a high priority for the overseeing officials.CONCLUSIONS: From a legal standpoint, OAT authorisations should be straightforward, yet we found significant divergences among cantonal systems. We could not find scientific evidence that supports a given framework. We recommend harmonizing the 26 cantonal systems while reviewing the need for OAT authorisation.